2015
DOI: 10.1007/s00382-015-2771-2
|View full text |Cite
|
Sign up to set email alerts
|

Centennial-scale teleconnection between North Atlantic sea surface temperatures and the Indian summer monsoon during the Holocene

Abstract: AMO), an alternative North Atlantic SST mode, with the NATS mode to determine their relationships to the ISM. A Holocene transient simulation indicates that the AMO's trend has diverged from that of the ISM since 5.5 ka BP, due to inverse SST trends over the tropical and extratropical North Atlantic. This latter trend leads to a much weaker relationship between the AMO and the ISM, relative to that observed between the NATS mode and the ISM. We therefore suggest that the centennial relationship between the Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…In addition, we would like to perform further comparisons between model results and proxy records to confirm our results as model-data comparisons can reduce the seasonal bias in proxy records Lohmann et al, 2013]. Mg/Ca records generally reveal warming trends in the subtropical and subpolar North Atlantic (north of 30°N) except the eastern part of the subtropical North Atlantic during the Holocene (Figure 1, Table 1), which fit well with modeled winter and spring SSTs (Figures 2a and 2b) but differ somewhat from summer SSTs [Zhang et al, 2015b] as estimated in the Kiel Climate Model (KCM) Holocene transient simulation (HT) simulation [Jin et al, 2014]. The warming trends in the subtropical and subpolar North Atlantic (north of 30°N) can be attributed to the increasing winter insolation ( Figure 3) [Liu et al, 2003;Came et al, 2007;Leduc et al, 2010].…”
Section: Sst Of the Subpolar North Atlantic Oceansupporting
confidence: 77%
“…In addition, we would like to perform further comparisons between model results and proxy records to confirm our results as model-data comparisons can reduce the seasonal bias in proxy records Lohmann et al, 2013]. Mg/Ca records generally reveal warming trends in the subtropical and subpolar North Atlantic (north of 30°N) except the eastern part of the subtropical North Atlantic during the Holocene (Figure 1, Table 1), which fit well with modeled winter and spring SSTs (Figures 2a and 2b) but differ somewhat from summer SSTs [Zhang et al, 2015b] as estimated in the Kiel Climate Model (KCM) Holocene transient simulation (HT) simulation [Jin et al, 2014]. The warming trends in the subtropical and subpolar North Atlantic (north of 30°N) can be attributed to the increasing winter insolation ( Figure 3) [Liu et al, 2003;Came et al, 2007;Leduc et al, 2010].…”
Section: Sst Of the Subpolar North Atlantic Oceansupporting
confidence: 77%
“…While in the northern part of the TP where the precipitation was dominated by the westerlies, Huang et al (2015) have found that the summer AMO index was significantly and positively correlated with summer precipitation (R 0.77, P < 0.01) as well. The connection of Atlantic SST variability, westerlies intensity and precipitation of the none-monsoon region of central Asia was reported (Li et al, 2008;Yu et al, 2014;Zhang et al, 2016;Luo et al, 2018). A positive or negative sign near the line between two variables indicates positive or negative correlations between them.…”
Section: Discussionmentioning
confidence: 89%
“…NEMO assumes 31 vertical levels. The KCM has been used for studies of internal climate variability (Park and Latif, 2008, 2010), external forced variability (Latif et al, 2009) and the Holocene Asian summer monsoon precipitation changes (Jin et al, 2014; Zhang et al, 2015). A detailed description of the KCM is given by Park et al (2009), including further information on the performance of the model.…”
Section: Methodsmentioning
confidence: 99%